Estudio de la herramienta map reduce y su utilización en la big data - Ramírez Palma, Aarón David (2023)
There is a paradigm that goes hand in hand with what is known as programming and parallel computing, which establishes a response inspired by the organization of data in enormous volumes. In this context, a framework that allows the processing of large amounts of data through parallel computing in distributed environments is incorporated into this research. As a result of what was expressed above, this research is focused on exploring how the Map Reduce tool is used in the management of Big Data and thereby providing significant information to undergraduate students in the use of this tool for the processing of large sets. . of data. This research is developed using the bibliographic method, framed in obtaining information from different sources that allow the purpose of the research to be fulfilled. It is also important to mention that the study focuses on the operation of the Map Reduce tool, with a point of More pragmatic view